A method for preparing a super-hydrophobic self-cleaning transparent ultra-thin coating and application of the coating

By preparing an Al2O3/ZnO self-cleaning coating with a needle-shaped array micro-nano structure on the surface of the photovoltaic panel and modifying perfluorodecyl triethoxysilane, the problem of dust accumulation in arid areas is solved, and the superhydrophobic dustproof and weather resistance of the coating is achieved.

CN117904597BActive Publication Date: 2025-02-28HARBIN INST OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410065588.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-17
Publication Date
2025-02-28
Estimated Expiration
2044-01-17

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prevent dust accumulation on the surface of photovoltaic panels in arid areas, and the superhydrophobic coating cannot be effectively cleaned under drought conditions.

Method used

Al2O3 film layer was prepared on the substrate surface by atomic layer deposition technology, and a needle-shaped array micro-nano structure was constructed through water bath etching. Combined with the reinforcement and protection of the ZnO film layer, the low surface energy modification was finally used to prepare a superhydrophobic self-cleaning transparent ultra-thin coating.

Benefits of technology

It can effectively prevent dust accumulation in arid areas. The coating has excellent super-hydrophobic dust resistance and weather resistance. It can automatically slide off dust under the action of wind and gravity, keeping the surface of the photovoltaic panel clean.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004667942170000011
    Figure HDA0004667942170000011
  • Figure HDA0004667942170000012
    Figure HDA0004667942170000012
  • Figure HDA0004667942170000013
    Figure HDA0004667942170000013
Patent Text Reader

Abstract

The present invention discloses a super-hydrophobic self-cleaning transparent ultra-thin coating and its preparation method and application, belonging to the technical field of functional material preparation. The present invention first uses atomic layer deposition technology to prepare a layer of Al2O3 thin film on the surface of the substrate, and then uses an etching method to construct a needle-shaped array micro-nano structure on the surface of the Al2O3 coating, and then uses the ALD technology to construct a ZnO coating to achieve the reinforcement and protection of the needle-shaped array, improve the weather resistance and firmness of the coating, and finally in order to further reduce the surface energy of the coating and reduce the adhesion of dust particles, perfluorodecyl triethoxysilane is used for low surface energy modification, and an Al2O3 / ZnO self-cleaning coating with excellent super-hydrophobic dustproof performance and weather resistance is prepared. In addition, the preparation method provided by the present invention has the advantages of simple process, easy availability of raw materials, and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a super-hydrophobic self-cleaning transparent ultra-thin coating and a preparation method and application thereof, and in particular to a super-hydrophobic self-cleaning and weather-resistant coating applied to the surface of a solar cell, belonging to the technical field of functional material preparation. Background Art

[0002] Energy is the material basis for the survival and development of human society, and it plays an important strategic role in the national economy. However, with the ever-expanding demand for energy, the reduction in the supply of traditional fossil energy with limited reserves, and the worsening environmental problems, the development of renewable energy is an irresistible trend. Among them, the photovoltaic power generation industry is also in a stage of large-scale development and high-quality development. As an important part of new energy, solar energy will show wider application potential in the future with its convenient access, sufficient energy, clean and green characteristics. However, in photovoltaic power generation, the optical system also faces many challenges. Among them, the accumulation of dust and foreign matter on the surface of photovoltaic panels is a huge problem, because their adhesion will cause damage to the photovoltaic power generation system.

[0003] Since most photovoltaic panels are exposed outdoors, atmospheric dust and foreign objects are important factors that affect the efficiency of photovoltaic panels. The dirt on photovoltaic panels seriously affects the quality of power generation. The reasons are: (1) Dust and foreign objects fall on the surface of the components and accumulate on the surface, increasing the thermal resistance of the photovoltaic components and affecting their heat dissipation; (2) Dust and foreign objects have a certain corrosive effect on the components, causing hot spots on the components, further reducing the output power of the components, and even affecting the life of the components; (3) The accumulation of foreign objects on the surface of the components blocks the light, affecting the absorption of solar energy by the photovoltaic panels, and reducing the efficiency of photovoltaic power generation. In view of the many adverse effects of dust accumulation on photovoltaic components, the cleaning of the photovoltaic surface is particularly important.

[0004] In order to reduce the adhesion of dust and foreign matter, existing solutions include manual cleaning, mechanical dust removal, and coating methods. The manual cleaning method refers to hiring workers to wipe and clean the surface of photovoltaic modules with a rag or brush with the assistance of tap water, but this method requires more water resources, has low cleaning efficiency, and is easy to scratch the surface, so the effect is not ideal; the mechanical cleaning method requires a mechanical device to clean dust and foreign matter, but this method is more complicated and requires additional equipment and maintenance. Therefore, the coating protection method has become a new option. The principle of this method is to apply a layer of special material on the surface of the photovoltaic panel to prevent the adhesion of dust and foreign matter, which has the advantages of low cost and less damage to the surface of the photovoltaic device. Among them, the super-hydrophobic coating can naturally roll off through water droplets under rainy conditions, taking away the dust on the surface. However, in arid areas, the super-hydrophobic coating may not be able to effectively prevent dust accumulation because dust may be embedded in the micro-nano structure of the coating. Therefore, it is urgent to design an appropriate microstructure to ensure that the dust on the surface of the super-hydrophobic coating can automatically slide off under the action of wind and gravity. Summary of the invention

[0005] In order to solve the above problems existing in the prior art, the present invention provides a super-hydrophobic self-cleaning transparent ultra-thin coating and a preparation method and application thereof.

[0006] The technical solution of the present invention:

[0007] One of the purposes of the present invention is to provide a method for preparing a super-hydrophobic self-cleaning transparent ultra-thin coating, the method comprising the following steps:

[0008] (1) ultrasonically cleaning the substrate and placing it in anhydrous ethanol for later use;

[0009] (2) performing atomic layer deposition on the pre-treated substrate to deposit an Al2O3 film on the surface of the substrate;

[0010] (3) The Al2O3 film obtained in (2) is subjected to water bath etching treatment.

[0011] (4) using atomic layer deposition technology to prepare a ZnO film layer on the Al2O3 film layer treated in (3);

[0012] (5) The whole is immersed in a n-hexane solution of perfluorodecyltriethoxysilane, then rinsed with n-hexane and dried to obtain a super-hydrophobic self-cleaning transparent ultra-thin coating.

[0013] It is further defined that the ultrasonic cleaning in (1) is: ultrasonic cleaning using anhydrous ethanol, acetone, deionized water and anhydrous ethanol in sequence for 15 minutes each.

[0014] It is further defined that in the atomic layer deposition process in (2), trimethylaluminum is used as the aluminum source, deionized water is used as the oxygen source, N2 is used as the load gas, the pressure in the reaction chamber is 0.1 torr, and the deposition temperature is 150°C.

[0015] Further defined, the process of each growth deposition cycle of the atomic layer deposition process in (2) is:

[0016] ① Inject aluminum source into the deposition chamber of the atomic layer deposition instrument in pulse form, the aluminum source temperature is 70-85°C, and the pulse time t1 is 0.03s;

[0017] ② Cut off the intake valve and exhaust valve to react, and the reaction time t2 is 6s;

[0018] ③Open the air inlet valve and exhaust valve, and purge with nitrogen. The purge time t3 is 40s;

[0019] ④ Inject an oxygen source into the deposition chamber in a pulsed form, the oxygen source temperature is room temperature, and the pulse time t4 is 0.02s;

[0020] ⑤Cut off the intake valve and exhaust valve to react, and the reaction time t5 is 6s;

[0021] ⑥Open the air inlet valve and the exhaust valve, and purge with nitrogen. The purge time t6 is 40s to complete a deposition growth cycle;

[0022] The growth and deposition cycles were repeated 77 times to obtain a substrate coated with an Al2O3 film layer.

[0023] It is further defined that the water bath etching treatment temperature in (3) is 95° C. and the time is 45 minutes.

[0024] It is further defined that in the atomic layer deposition process in (4), diethyl zinc is used as the zinc source, deionized water is used as the oxygen source, N2 is used as the load gas, the pressure in the reaction chamber is 0.1 torr, and the deposition temperature is 150°C.

[0025] Further defined, the process of each growth deposition cycle of the atomic layer deposition process in (4) is:

[0026] ① Inject a zinc source into the deposition chamber of the atomic layer deposition instrument in a pulsed form, the zinc source temperature is 70-85°C, and the pulse time t1 is 0.02s;

[0027] ② Cut off the intake valve and exhaust valve to react, and the reaction time t2 is 6s;

[0028] ③Open the air inlet valve and exhaust valve, and purge with nitrogen. The purge time t3 is 40s;

[0029] ④ Inject an oxygen source into the deposition chamber in a pulsed form, the oxygen source temperature is room temperature, and the pulse time t4 is 0.02s;

[0030] ⑤Cut off the intake valve and exhaust valve to react, and the reaction time t5 is 6s;

[0031] ⑥Open the air inlet valve and the exhaust valve, and purge with nitrogen. The purge time t6 is 40s to complete a deposition growth cycle;

[0032] The growth and deposition cycles were repeated 58 times to obtain a ZnO film layer.

[0033] It is further defined that the immersion time in (5) is 30 minutes, the drying temperature is 80°C, and the drying time is 1 hour.

[0034] The second object of the present invention is to provide a super-hydrophobic self-cleaning transparent ultra-thin coating obtained by the above preparation method, and the coating thickness is 30nm.

[0035] It is further defined that the coating is used on the surface of a solar cell.

[0036] Beneficial effects:

[0037] The present invention first uses atomic layer deposition technology to prepare a layer of Al2O3 film on the surface of the substrate, then uses an etching method to construct a needle array micro-nano structure on the surface of the Al2O3 coating, and then uses the ALD technology to construct a ZnO coating to achieve reinforcement and protection of the needle array, improve the weather resistance and robustness of the coating, and finally, in order to further reduce the surface energy of the coating and reduce the adhesion of dust particles, perfluorodecyl triethoxysilane is used for low surface energy modification to prepare an Al2O3 / ZnO self-cleaning coating with excellent super-hydrophobic dustproof performance and weather resistance. In addition, the preparation method provided by the present invention has the advantages of simple process, easy availability of raw materials, and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a SEM photo of the Al2O3 film layer prepared in Example 1;

[0039] Figure 2 This is a SEM photo of the Al2O3 film obtained in Example 1 after being treated with water bath etching;

[0040] Figure 3 The transmittance curves and transmittance comparison curves of Al2O3 films of different thicknesses prepared in Examples 1 to 6;

[0041] Figure 4 The transmittance curves and transmittance comparison curves of the coatings prepared in Examples 1 and 7 to 11 with different water bath etching times;

[0042] Figure 5The transmittance curves and transmittance comparison curves of the composite coatings with different ZnO film thicknesses prepared in Examples 1 and 12 to 15;

[0043] Figure 6 This is a test diagram of the dustproof performance of the super hydrophobic self-cleaning coating prepared in Example 1;

[0044] Figure 7 This is a water contact angle test diagram of the super hydrophobic self-cleaning coating prepared in Example 1;

[0045] Figure 8 This is a comparison chart of the weather resistance test results of the super-hydrophobic self-cleaning coating prepared in Example 1. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0047] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0048] Embodiment 1:

[0049] 1. Substrate pretreatment

[0050] The substrate is a Φ5cm quartz glass specimen, and the glass substrate is ultrasonically cleaned:

[0051] The quartz glass specimen was ultrasonically cleaned with anhydrous ethanol, acetone, deionized water and anhydrous ethanol for 15 min in sequence, and then placed in a beaker containing anhydrous ethanol for later use.

[0052] 2. Coating Preparation

[0053] In the first step, an Al2O3 transition layer film with a thickness of 20 nm was prepared using atomic layer deposition technology, with trimethylaluminum as the Al source, deionized water as the O source, N2 as the load gas, the pressure in the reaction chamber being 0.1 torr, and the deposition temperature range being 150°C for atomic layer deposition treatment.

[0054] The process of each growth and deposition cycle is:

[0055] ① Inject aluminum source into the deposition chamber of the atomic layer deposition instrument in pulse form, the aluminum source temperature is 70-85°C, and the pulse time t1 is 0.03s;

[0056] ② Cut off the intake valve and exhaust valve to react, and the reaction time t2 is 6s;

[0057] ③Open the air inlet valve and exhaust valve, and purge with nitrogen. The purge time t3 is 40s;

[0058] ④ Inject an oxygen source into the deposition chamber in a pulsed form, the oxygen source temperature is room temperature, and the pulse time t4 is 0.02s;

[0059] ⑤Cut off the intake valve and exhaust valve to react, and the reaction time t5 is 6s;

[0060] ⑥Open the air inlet valve and the exhaust valve, and purge with nitrogen. The purge time t6 is 40s to complete a deposition growth cycle;

[0061] The growth and deposition cycles were repeated 77 times to obtain an Al2O3 film with a thickness of 20 nm on the quartz glass test piece.

[0062] The surface microstructure of the Al2O3 film was characterized. Figure 1 shown.

[0063] In the second step, the Al2O3 film with a thickness of 20 nm was etched in a water bath at a temperature of 95°C for 45 min to obtain a high-transmittance coating with a needle-shaped array micro-nano structure.

[0064] The surface microstructure of the Al2O3 film after water bath etching was characterized. Figure 2 As shown, compared Figure 1 and Figure 2 It can be seen that the surface of the unetched Al2O3 film is smooth, without cracks, wrinkles, protrusions and other rough structures. The acid-etched Al2O3 sample presents a needle array structure.

[0065] In the third step, atomic layer deposition technology is used to prepare a ZnO functional layer film with a thickness of 10 nm, using diethyl zinc as the zinc source, deionized water as the oxygen source, N2 as the load gas, the pressure in the reaction chamber is 0.1 torr, and the deposition temperature is 150°C for atomic layer deposition treatment.

[0066] The process of each growth and deposition cycle is:

[0067] ① Inject a zinc source into the deposition chamber of the atomic layer deposition instrument in a pulsed form, the zinc source temperature is 70-85°C, and the pulse time t1 is 0.02s;

[0068] ② Cut off the intake valve and exhaust valve to react, and the reaction time t2 is 6s;

[0069] ③Open the air inlet valve and exhaust valve, and purge with nitrogen. The purge time t3 is 40s;

[0070] ④ Inject an oxygen source into the deposition chamber in a pulsed form, the oxygen source temperature is room temperature, and the pulse time t4 is 0.02s;

[0071] ⑤Cut off the intake valve and exhaust valve to react, and the reaction time t5 is 6s;

[0072] ⑥Open the air inlet valve and the exhaust valve, and purge with nitrogen. The purge time t6 is 40s to complete a deposition growth cycle;

[0073] The growth and deposition cycles were repeated for 58 times to obtain a ZnO film layer with a thickness of 10 nm.

[0074] In the fourth step, the coating was immersed in a 2% perfluorodecyltriethoxysilane n-hexane solution for 30 minutes, then rinsed with n-hexane and heated at 80°C for 1 hour to obtain a super-hydrophobic self-cleaning transparent ultra-thin coating.

[0075] Embodiment 2:

[0076] The difference between this embodiment and embodiment 1 is that the first step repeats 39 growth and deposition cycles, and the remaining process steps and parameter settings are the same as those of embodiment 1. An Al2O3 film with a thickness of 5 nm is obtained on the quartz glass test piece.

[0077] Embodiment 3:

[0078] The difference between this embodiment and the embodiment is that the first step is to repeat 77 growth and deposition cycles, and the remaining process steps and parameter settings are the same as those of embodiment 1. An Al2O3 film with a thickness of 10 nm is obtained on a quartz glass test piece.

[0079] Embodiment 4:

[0080] The difference between this embodiment and embodiment 1 is that the first step is to repeat 230 growth and deposition cycles, and the remaining process steps and parameter settings are the same as those of embodiment 1. An Al2O3 film with a thickness of 30 nm is obtained on the quartz glass test piece.

[0081] Embodiment 5:

[0082] The difference between this embodiment and embodiment 1 is that the first step is repeated for 307 growth and deposition cycles, and the remaining process steps and parameter settings are the same as those of embodiment 1. An Al2O3 film with a thickness of 40 nm is obtained on the quartz glass test piece.

[0083] Embodiment 6:

[0084] The difference between this embodiment and embodiment 1 is that the first step is to repeat 384 growth and deposition cycles, and the remaining process steps and parameter settings are the same as those of embodiment 1. An Al2O3 film with a thickness of 50 nm is obtained on the quartz glass test piece.

[0085] The transmittance of the Al2O3 films of different thicknesses obtained in Examples 1 to 6 in the visible light band (400-1100nm) was characterized by a UV-visible spectrophotometer. The results are as follows: Figure 3 shown.

[0086] Embodiment 7:

[0087] The difference between this embodiment and embodiment 1 is that the water bath etching time of the second step is 15 minutes, and the other process steps and parameter settings are the same as those of embodiment 1.

[0088] Embodiment 8:

[0089] The difference between this embodiment and embodiment 1 is that the water bath etching time of the second step is 30 minutes, and the other process steps and parameter settings are the same as those of embodiment 1.

[0090] Embodiment 9:

[0091] The difference between this embodiment and the embodiment is that the water bath etching time of the second step is 60 minutes, and the remaining process steps and parameter settings are the same as those of embodiment 1.

[0092] Embodiment 10:

[0093] The difference between this embodiment and embodiment 1 is that the water bath etching time in the second step is 75 minutes, and the other process steps and parameter settings are the same as those in embodiment 1.

[0094] Embodiment 11:

[0095] The difference between this embodiment and embodiment 1 is that the water bath etching time in the second step is 0 min, and the other process steps and parameter settings are the same as those in embodiment 1.

[0096] The transmittance of the coatings obtained in Examples 1 and 7 to 11 with different water bath etching times in the visible light band (400-1100 nm) was characterized by a UV-visible spectrophotometer. The results are as follows: Figure 4 shown.

[0097] Embodiment 12:

[0098] The difference between this embodiment and embodiment 1 is that the third step is repeated for 30 growth and deposition cycles, and the remaining process steps and parameter settings are the same as those of embodiment 1. A ZnO film with a thickness of 5 nm is obtained on the quartz glass test piece.

[0099] Embodiment 13:

[0100] The difference between this embodiment and embodiment 1 is that the third step is repeated for 88 growth and deposition cycles, and the remaining process steps and parameter settings are the same as those of embodiment 1. A ZnO film with a thickness of 15 nm is obtained on the quartz glass test piece.

[0101] Embodiment 14:

[0102] The difference between this embodiment and embodiment 1 is that the third step is repeated for 118 growth and deposition cycles, and the remaining process steps and parameter settings are the same as those of embodiment 1. A ZnO film with a thickness of 20 nm is obtained on the quartz glass test piece.

[0103] Embodiment 15:

[0104] The difference between this embodiment and embodiment 1 is that the third step repeats 0 growth and deposition cycles, and the remaining process steps and parameter settings are the same as those of embodiment 1. A ZnO film layer with a thickness of 0 nm is obtained on the quartz glass test piece.

[0105] The transmittance of the coatings obtained in Examples 1 and 12 to 15 with different water bath etching times in the visible light band (400-1100 nm) was characterized by a UV-visible spectrophotometer. The results are as follows: Figure 5 shown.

[0106] From the above data, it can be seen that in the 400-1100nm band, the Al2O3 film thickness of 20nm, the water bath etching time of 45min and the temperature of 95℃ are selected as the structure of the transition layer film. Combined with the subsequent weather resistance test, the ZnO functional layer film thickness of 10nm is selected. At this time, the super-hydrophobic self-cleaning coating obtained can achieve high light transmittance and good weather resistance at the same time.

[0107] In order to explore the dust removal performance of the composite coating, the dust removal performance of the super hydrophobic self-cleaning coating prepared in Example 1 was tested using a homemade dust removal angle test device. Volcanic ash was placed on the test platform, a rotating device was used, and the rotation angle when the dust fell was observed to test the dust removal performance. After testing, it was found that the dust on the surface of the coating all slid off at a very small inclination angle. From the test results, it can be seen that the super hydrophobic self-cleaning coating prepared by the present invention has a complete dust removal angle of 45.4°, and the coating has excellent dust-proof performance. The results are as follows Figure 6 shown.

[0108] The effect of the super hydrophobic self-cleaning coating prepared in Example 1 on the hydrophobic performance of the solar photovoltaic panel was measured by a water contact angle tester. The results are as follows Figure 7 As shown, from the test results, it can be seen that the water contact angle of the super hydrophobic self-cleaning coating prepared in Example 1 is 156°, and the coating has excellent super hydrophobic properties.

[0109] Since the dust adhered to the surface of the photovoltaic panel under actual conditions will cause certain wear and tear on the surface of the photovoltaic panel, in order to test the weather resistance of the super hydrophobic self-cleaning coating prepared in Example 1, the sample glass was turned upside down on the surface of 400-mesh sandpaper, and a 100g weight was pressed on the back of the sample. The sample and the weight were pushed to move on the sandpaper surface. The dust removal angle of the composite coating was tested after each movement of 20cm until there were obvious signs of wear on the surface of the composite coating. The dustproof performance and hydrophobic angle of the coating after wear were tested. The test results are as follows: Figure 8 As shown, the test results show that the super hydrophobic self-cleaning coating prepared in Example 1 has good weather resistance.

[0110] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a super-hydrophobic self-cleaning transparent ultra-thin coating, characterized in that: include: (1) ultrasonically cleaning the substrate and placing it in anhydrous ethanol for later use; (2) performing atomic layer deposition on the pre-treated substrate to deposit an Al2O3 film on the surface of the substrate; (3) subjecting the Al2O3 film obtained in (2) to water bath etching; The water bath etching treatment temperature is 95°C and the time is 45 minutes; (4) using atomic layer deposition technology to prepare a ZnO film layer on the Al2O3 film layer treated in (3); (5) immersing the whole in a n-hexane solution of perfluorodecyltriethoxysilane, then rinsing with n-hexane, and drying to obtain a super-hydrophobic self-cleaning transparent ultra-thin coating with a thickness of 30 nm; The soaking time is 30 minutes, the drying temperature is 80°C, and the time is 1 hour.

2. The preparation method according to claim 1, characterized in that: (1) Ultrasonic cleaning is as follows: use anhydrous ethanol, acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 15 minutes each.

3. The preparation method according to claim 1, characterized in that: (2) During the atomic layer deposition process, trimethylaluminum was used as the aluminum source, deionized water was used as the oxygen source, N2 was used as the load gas, the pressure in the reaction chamber was 0.1 torr, and the deposition temperature was 150°C.

4. The preparation method according to claim 3, characterized in that: The process of each growth and deposition cycle of the atomic layer deposition process in (2) is: ① Inject aluminum source into the deposition chamber of the atomic layer deposition instrument in pulse form, the aluminum source temperature is 70-85°C, and the pulse time t1 is 0.03s; ② Cut off the intake valve and exhaust valve to react, and the reaction time t2 is 6s; ③Open the air inlet valve and exhaust valve, and purge with nitrogen. The purge time t3 is 40s; ④ Inject an oxygen source into the deposition chamber in a pulsed form, the oxygen source temperature is room temperature, and the pulse time t4 is 0.02s; ⑤Cut off the intake valve and exhaust valve to react, and the reaction time t5 is 6s; ⑥Open the air inlet valve and the exhaust valve, and purge with nitrogen. The purge time t6 is 40s to complete a deposition growth cycle; The growth and deposition cycles were repeated 77 times to obtain a substrate coated with an Al2O3 film layer.

5. The preparation method according to claim 1, characterized in that: (4) During the atomic layer deposition process, diethyl zinc was used as the zinc source, deionized water was used as the oxygen source, N2 was used as the load gas, the pressure in the reaction chamber was 0.1 torr, and the deposition temperature was 150°C.

6. The preparation method according to claim 5, characterized in that: The process of each growth and deposition cycle of the atomic layer deposition process in (4) is: ① Inject a zinc source into the deposition chamber of the atomic layer deposition instrument in a pulsed form, the zinc source temperature is 70-85°C, and the pulse time t1 is 0.02s; ② Cut off the intake valve and exhaust valve to react, and the reaction time t2 is 6s; ③Open the air inlet valve and exhaust valve, and purge with nitrogen. The purge time t3 is 40s; ④ Inject an oxygen source into the deposition chamber in a pulsed form, the oxygen source temperature is room temperature, and the pulse time t4 is 0.02s; ⑤Cut off the intake valve and exhaust valve to react, and the reaction time t5 is 6s; ⑥Open the air inlet valve and the exhaust valve, and purge with nitrogen. The purge time t6 is 40s to complete a deposition growth cycle; The growth and deposition cycles were repeated 58 times to obtain a ZnO film layer.

7. An application of a super-hydrophobic self-cleaning transparent ultra-thin coating prepared by the method according to claim 1, characterized in that: Used on the surface of solar cells.

Citation Information

Patent Citations

  • Preparation method of self-cleaning hydrophobic film for electronic screen

    CN110747449A

  • High-permeability hydrophobic dustproof film and preparation method thereof

    CN113877785A

  • Preparation method of aluminum-doped zinc oxide film

    CN115652277A

  • Protective coated object and method of coating an object

    US20160060758A1